Evaluación del material particulado que se genera en la elaboración de balanceados en la planta Cantapez Aves y Pez cantón CÍA. LTDA., y su incidencia en la salud de los trabajadores. - Erazo Solórzano, Cyntia Yadira (2017)
This research indicates an alternative to reduce air pollution in a feed processing plant in Ecuador, and its objective is to determine the type of particles present in the air, take preventive measures to minimize their impact on the health of workers. Field research is carried out for the collection of information applying the interview, survey and observation sheet techniques, through the initial risk matrix the critical points of the process are determined and the respective measurements of the amount of total suspended particles in the work environment are made.